CRITICAL STUDIES OF INDONESIA’S INTEREST IN RATIFICATION PROCESS OF THE 1951 CONVENTION AND 1967 PROTOCOL - M. Alvi Syahrin; Surya Pranata (Jurnal Ilmiah Kajian Keimigrasian, 2018)
The increasing number of refugees each year has caused the government difficulties in handling refugee issues. The absence of law concerning refugees in Indonesia has caused weak coordination between related institutions in field. In this paper will discuss what the urgency, relevance, and obstacles faced by Indonesia in the process of ratification of the 1951 Convention and 1967 Protocol. The research method used in this paper is qualitative normative legal research method with deductive logical thingking. The urgency to ratify this Convention can strengthen the human rights institutions in the country, although this is not the only indicator for good human rights implementation. It is because some human rights norms are in fact also regulated in domestic legislation in the current reform era this. Indonesia can not exclude the existence of the International Convention on Human Rights. Even it is necessary to bring the domestic and international factors closer. The relevance to ratify this Convention will enhance the international accountability of a country through a more objective and civilized way. Meanwhile, in terms of legal technical considerations, the ratification will strengthen and enrich the national legal instruments so that it will better ensure the progress and protection of human rights better. Ratification can even be a shortcut to bring closer the existing gap between legal instruments at the international and national levels. Obstacles faced are categorized into two aspects, namely the security and legal aspects. The security aspect caused by refugees is often seen as a threat to the state. While the legal aspects of the law are caused by the absence of comprehensive rules in regulating the refugees and asylum seekers in positive law in Indonesia that can weaken the coordination between agencies in the field. As a law-based country that highly appreciate human rights, ratification of The 1951 Refugee Convention and 1967 Protocol must be a priority. Both instruments are relevant, since the substance are not only heavily loaded with regulation about human rights but also in line with cultural values and norms in Indonesia. As such, the process of ratification needs to consider the country readiness, in terms of technical, political and legal aspects, since those aspects are sometimes challenging. On this matter, ratification is expected to narrow the gap between national and international instruments of law.